The Practice-oriented Model of «School Psychology» Master's Program - Andruschenko T.Y; Shashlova G.M; Shubina A.S (Moscow State University of Psychology and Education, 2015)
We presented the experience in the development and testing the module "Psychological diagnosis of students" of the "School psychology" master program in "Psychological and pedagogical education" training direction. We discussed contemporary contexts of design educational modules that are defined by ideas of cultural-historical approach of the scientific school of L.S. Vygotsky, educational theories and activities of developing education by D.B. Elkonin, V.V. Davydov, collectively distributed educational activity of V.V. Rubtsov. We analyzed the issue of professional competence training in educational psychologists at higher education. We presented the connection between the content of masters training and the requirements of the Professional standard "Teacher-psychologist (the psychologist in education)". Within the context of the network of educational organizations we paid special attention to the content and organization of distributed practice as the basic condition of master's professional competences formation and their readiness for the implementation of the working activities.